ANALISA RUGI-RUGI DAYA (LOSSES POWER) PADA JARINGAN TEGANGAN RENDAH PT. MUSIMAS BATAM - Muhammad Irsyam; Missyamsu Algusri; Linggom Pandapotan Marpaung (SIGMA TEKNIKA, 2023)
PT. MUSIMMAS BATAM is one of the largest integrated palm oil companies in the world that requires a three-phase voltage supply of approximately 250 amperes for each phase. PT. Musimmas Batam is supplied from a 150,000 KVA transformer through the LVMDP Panel, with priority on supplying electricity needs. The 3-phase voltage values are obtained, namely: R-S = 404.4 V, R-T = 404.2 V, S-T = 404.1 V with a neutral voltage of R-N = 23.2 V, S-N = 23.1, T-N = 23.3. And the 3-phase current IR = 202.9 Amperes, IS = 213.7 Amperes, IT = 200.7 Amperes. Total Power Calculation at LVMDP based on the equation looking for Iaverage = 205.7 A, Based on the equation looking for Vaverage = 1212.7 V, Based on the equation looking for P = 241.9 Kw. Power losses for a 400 mm² wire (R = 0.047 Ω/km) is 46.6 watts/km = 0.046 kW/km, and the total length of the conductor cable from the LVMDP Panel to the Load  500 M with the calculation of power losses, namely : P = 4833 watts/km. While the total power supply is 8.0 Kw = 8000 watts, so it can be seen = 3167 watts/km (3.16 Kw). Where is the active power of the transformer (P) = 145.5 kW. Thus, the percentage of losses due to neutral currents in the neutral conductor of the transformer is 0.03%.Key word : LVMDP Panels, Cables, Loads